2004
DOI: 10.1038/sj.eye.6701392
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine 0.2% vs unoprostone 0.15% both added to timolol maleate 0.5% given twice daily to patients with primary open-angle glaucoma or ocular hypertension

Abstract: Purpose To compare the efficacy and safety of brimonidine 0.2% vs unoprostone 0.15%, both added to timolol maleate 0.5% each given twice daily. Methods In this prospective, multi-centred, double-masked, crossover comparison, patients were randomized to one treatment group for a 6-week treatment period, and then crossed over to the opposite treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, adjunctive therapy between these medicines was not evaluated. Brimonidine has been shown to be effective throughout the 12-hour diurnal curve when given twice daily and added to timolol, and may have improved its late afternoon performance against unoprostone if both had been added to timolol maleate (Sharpe et al 2004). Further study may clarify the advantages and disadvantages of brimonidine versus unoprostone in the treatment of ocular hypertension or glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adjunctive therapy between these medicines was not evaluated. Brimonidine has been shown to be effective throughout the 12-hour diurnal curve when given twice daily and added to timolol, and may have improved its late afternoon performance against unoprostone if both had been added to timolol maleate (Sharpe et al 2004). Further study may clarify the advantages and disadvantages of brimonidine versus unoprostone in the treatment of ocular hypertension or glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…6769 In a 12-week, multicenter, double-masked, randomized trial of 146 patients comparing unoprostone, brimonidine, and dorzolamide when added to timolol, Hommer et al found comparable efficacy in mean diurnal IOP reduction between all groups, with each adjunctive agent producing an additional drop in IOP of 2–3 mmHg from a timolol-treated baseline (see Figure 3). 67 Similar results were found in two other studies comparing unoprostone, brimonidine, and dorzolamide as adjunctive therapy with timolol 68,69. A study by Saito et al involving 52 patients with primary open-angle glaucoma found no additional IOP-lowering effect when unoprostone was added to latanoprost following 12 weeks of therapy 53…”
Section: Efficacymentioning
confidence: 99%